School Teachers’ Knowledge and Attitude towards Mental Disorders among Schoolgoing Children: A Cross-sectional Study - Lubna Tyagdal; Akshay Shreekrishna Phatak (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Mental disorders in children can present with non specific behavioural issues, like irritability and procrastination. These issues are often neglected, which can negatively affect academic performance and overall development. Teachers hold a unique position to promote mental health and facilitate early identification of mental disorders, leading to timely referrals for early intervention. Aim: To examine the knowledge and attitude of school teachers towards mental disorders in school-going children. Materials and Methods: A cross-sectional study was conducted in Karwar city over a period of two months (July and August 2019) at the Karwar Institute of Medical Sciences, Karnataka , India. A total of 121 primary and high school teachers from 11 schools participated in the study. Purposive sampling was used, as all schools in Karwar city were approached for the study. A self-designed questionnaire consisting of 20 questions (10 questions on knowledge and 10 questions on attitude towards children with mental disorders) was used. Descriptive statistics, such as percentages, were used for data analysis. Results: The study revealed that teachers had moderate knowledge about child mental disorders. However, there was a lack of awareness about the treatment and care of such children. Sixty-three (52.07%) teachers believed that mental disorders result from incorrect thinking. Seventy-nine (65.29%) teachers were of the opinion that sleeping pills are not the only available treatment. Attitude towards children with mental disorders were both positive and negative. 82 (67.77%) teachers believed such children to be less intelligent, while 76 (62.81%) teachers did not believe mentally ill children indulge in violence. Many teachers were aware that these children can be vulnerable to bullying and discrimination by their peers. Conclusion: The study concluded that there is moderate knowledge and mixed attitude among school teachers regarding mental disorders in school-going children. This highlights the need for proper training programs that can aid in early identification, timely referrals for mental health evaluation, and the promotion of child mental health.